A secure image encryption based on spatial surface chaotic system and AES algorithm - Sun, Fuyan; Lv, Zongwang (Multimedia tools and applications, 2022)
We propose a secure image encryption method using the combination of spatial surface chaotic system(SSCS) and the improved AES algorithm structure. In this scheme, the key of cryptosystem is obtained from the SSCS, this system has better encryption characteristics and its model structure fits the image exactly, and it is designed for image cryptosystems contrasted with the existing a lot of low-dimensional chaotic maps and couple map lattices. The plain image is encrypted with the improved AES algorithm and by performing each round encryption, the key is generated by SSCS in each round, an improved permutation algorithm(IPA) and a reverse diffusion have been presented. The proposed scheme not only improves the efficiency because of the same key stream is shared, but also increases the diffusion effect which can resist differential attack. The presented scheme provides huge key space to deal with the brute-force attacks using the round keys obtained by SSCS, and also very sensitive to initial values of SSCS and plain image. The results of simulation analysis and performance evaluation show that the presented cryptosystem provides strong security performance and may be used as a candidate for real-time implementations.